The Impact of Artificial Intelligence (AI) Capability on Service Innovation in Public Sector of Malaysia: A Proposed Conceptual Model - Khin, Sabai; Mustafar, Muhammad Rajaie (Journal of International Conference Proceedings, 2024)
Although AI has become an important technology in augmenting human interactions with customers, only a few studies have linked AI capability to service innovation, leaving a gap in understanding of how AI can enhance service innovation in the context of government sector. To address this gap, this study proposes a new conceptual model that is appropriate to test the effect of AI capability on service innovation, and moderating effect of workforce agility on such effect. This study is one of the first studies linking AI capability and service innovation by uncovering the contingency role of workforce agility.Â